COVID-associated cognitive impairments: A review - Irina S. Preobrazhenskaya (ZAO "Consilium Medicum", 2022)
The COVID-19 pandemic, caused by the SARS-CoV-2 virus, began in March 2020 and continues to the present. The virus most often affects the respiratory system; to date, there is evidence of possible damage to the heart, skin, kidneys, central nervous system in this disease. In this regard, it is of great interest to study the neurological features of COVID-19, in particular, the development of cognitive disorders or the increase in the severity of already existing cognitive impairments. This review provides the latest data on the relationship of COVID-19 and cognitive impairment, the proposed etiology, pathogenesis and main clinical manifestations of cognitive disorders, and also discusses possible strategies for the treatment of cognitive impairment after suffering COVID-19.